Volatilidad de tipo de cambio y dolarización de empresas bancarias del sistema financiero peruano, 2012 - 2018 - Yauri Lozano, Emerson (2020)
The dollarization of the banking companies of the financial system have strong implications in the development and decision making of these to generate “mismatches” both currencies and terms, having incidence in the administration, planning, cost management, risk and others that finally affects the economic financial results of these companies. There are many causes that explain dollarization in banking companies. According to the seen in many countries, mainly developing countries and small economies, the volatility of the exchange rate has played an important role in the behavior of dollarization. The main results of the study are: the volatility of the exchange rate significantly influences the dollarization of the banking companies of the Peruvian financial system during the period 2012-2018; In turn, it significantly affects the dollarization of credits and dollarization of deposits.